Genetic diversity of Olive flounder (Paralichthys olivaceus) and the impact of selective breeding on Korean populations - Euiseo Hong; Hyun-Chul Kim; Jeong-Ho Lee; Woonyoung Jeong; Phuong Thanh N. Dinh; Waruni Ekanayake; Jong-Won Park; Minhwan Jeong; Dain Lee; Julan Kim; Yoonsik Kim; Seung Hwan Lee; et al. (PLoS ONE, 2025)
This study aimed to identify the population structure and genetic diversity of olive flounder (Paralichthys olivaceus) in Korea and to examine the potential for genetic improvement in aquaculture populations. PCA showed NIFS and FarmA as closely related clusters, while FarmB exhibited moderate differentiation with greater variability. Fst analysis indicated high similarity between NIFS and farmed populations (0.021–0.043) but significant differentiation from wild populations (0.274–0.295). Admixture analysis highlighted a shared ancestral component (over 70%) among NIFS and farmed populations, contrasting with the unique genetic makeup of wild populations. The phylogenetic tree confirmed these patterns, with NIFS and FarmA forming close branches, FarmB showing intermediate placement, and wild populations clustering separately. Additionally, genomic estimated breeding values for body weight showed no significant differences between FarmA and FarmB, while prediction accuracy was higher for FarmA (47%) compared to FarmB (45%), indicating a closer genetic relationship between NIFS and FarmA. These findings emphasize the critical role of selective breeding and gene flow in shaping the genetic structure of farmed populations, offering valuable insights for improving growth traits and maintaining genetic diversity in aquaculture.